Titanium Nanoparticles Modified NIR Emission of Neodymium Doped Magnesium Zinc-Sulfophosphate Glass: Effect of Heat Treatment on Surface Plasmon Resonance Bands. Issue 1 (1st December 2022) - Yusof, N N; Hashim, S; Aziz, S M; Azlan, M N; Iskandar, S M; Zaid, M H M; Hisam, R; Nazrin, S N; Yusoff, N M
Abstract: New type plasmonic sensitizer, titanium nanoparticles (Ti NPs) shown potential in enhancing photoluminescence of rare-earth ions (REIs) as doped into magnesium zinc-sulfophosphate (MZS) glass for optical to optic application. Here, neodymium ions (Nd 3+ )-doped MZS glass with Ti NPs inclusion gone heat treatment (HT) at 450°C for 6 and 12 hours in order to tune the NPs size and tailor their plasmonic strength. The sample was characterized using X-ray diffractometer (XRD), high-resolution transmission electron microscope (HRTEM), and photoluminescence (PL) spectrometer. Heat treatment (HT) grows Ti NPs with a mean size ≈ 16 nm. The SPR bands are probed around 585and 739 nm. The SPR band intensities change with HT duration. The NIR PL bands were perceived around 878 nm, 1050 nm and 1322 nm corresponding to 4 F3/2 → 4 I9/2, 4 F3/2 → 4 I11/2 and 4 F3/2 → 4 I 13/2 transitions, accordingly. The PL transition 4 F3/2 → 4 I9/2 (878 nm) and 4 F3/2 → 4 I13/2 (1322 nm) is enhanced about 1.44 and 1.52 times respectively, after 12 hours HT. The results show that HT enhances PL through SPR amplification. These findings may be useful in developing solid-state lasers and optical materials.